The relationship between sports participation and bullying in elementary schools: the mediating role of mental toughness - Ma, Changhao; Gao, Mingze; Qi, Ziyang; Che, Wen; Qi, Shenghua (Frontiers in Psychology, 2025)
PurposePrevious research has shown a correlation between sports participation and bullying in schools. However, less attention has been paid to the factors influencing children’s perpetrated bullying and victimized. Therefore, this study constructed a model of the role of influencing factors between sports participation, children’s mental toughness, and school bullying to explore the link between sports participation and mental toughness on children’s perpetrated bullying and victimized.MethodsA sample of 861 students was randomly selected from five elementary schools in Shandong Province, China. After excluding invalid questionnaires with missing answers or consistent responses, 712 questionnaires were collected. The Physical Activity Rating Scale (PARS-3) was selected to assess sports participation, the Mental Toughness Scale to evaluate mental resilience, and the Chinese-adapted version of the Oweis Bullying Questionnaire (OBQ), which was revised by Chinese scholar Zhang Xinwen, to measure bullying experiences. All participants completed maturation scales on sports participation, mental toughness, and school bullying. Data were analyzed in SPSS 24.0, SPSSprocess 4.1, and AMOS 27.ResultsThe results of this study are as follows: (1) According to the correlation test results, since p < 0.05 or p < 0.01, there is a correlation between sports participation and psychological resilience, bullying and being bullied. There is a correlation between mental resilience and bullying, being bullied. There is a correlation between bullying and being bullied. (2) Mental toughness plays a mediating role in the influence of sports participation on the perpetrated bullying and in the influence of sports participation on victimized. (3) In the pathways of sports participation, mental toughness, and school bullying, it suggested that mental toughness played a partial mediating role in this pathway. For the pathways of sports participation, mental toughness, and children’s exposure to bullying. The mental toughness played a full mediating role in this pathway.ConclusionIt is recommended that early intervention and support be given to promote children’s physical mobility and increase their own levels of sports participation and mental toughness, thereby reducing the likelihood of children committing or experiencing bullying in schools and improving their physical and mental health.